Distribution and predictors of urinary polycyclic aromatic hydrocarbon metabolites in two pregnancy cohort studies. (January 2018) - Cathey, Amber; Ferguson, Kelly K.; McElrath, Thomas F.; Cantonwine, David E.; Pace, Gerry; Alshawabkeh, Akram; Cordero, Jose F.; Meeker, John D.
Abstract: Pregnant women and their fetuses represent susceptible populations to environmental contaminants. Exposure to polycyclic aromatic hydrocarbons (PAHs) among pregnant women may contribute to adverse birth outcomes such as preterm birth. Multiple previous studies have assessed airborne sources of PAHs among pregnant women but few have measured urinary PAH metabolites which can capture total exposure through multiple routes. The aim of this study was to bridge this knowledge gap by assessing longitudinal urinary PAH metabolite concentrations over two time points in pregnancy cohorts in Boston (N = 200) and Puerto Rico (N = 50) to better understand exposure distributions throughout pregnancy and how they relate to demographic factors. Urine samples were analyzed for 1-NAP, 2-NAP, 2-FLU, 1-PHE, 2, 3-PHE, 4-PHE, 9-PHE, and 1-PYR. Concentrations of 2-NAP, 1-PYR, and 4-PHE were higher in Puerto Rico, while all other metabolites were present in higher concentrations in Boston. In Puerto Rico, intraclass correlation coefficients (ICC) were weak to moderate, ranging from 0.06 to 0.42. PAH metabolite concentrations were significantly higher among younger, heavier (except 1-NAP and 9-PHE), and less educated individuals in Boston only. Consistent significant associations between PAH concentrations and measured covariates were not found in Puerto Rico. Our results suggest that potentially important differences in PAH exposure exist between these two populations. Additionally, our results indicate that multiple urinary measurements are required to accurately assess PAH exposure throughout pregnancy. Graphical abstract: Highlights: PAH metabolites are detected in most urine samples in 2 distinct pregnancy cohorts. High BMI and young age are associated with higher levels of some PAH metabolites. Multiple measurements are necessary to accurately estimate gestational PAH exposure. Abstract : Pregnant women in Boston and Puerto Rico are differentially exposed to polycyclic aromatic hydrocarbons, with some biomarker levels being associated with younger age and higher BMI.